Assisting novice researchers in utilizing the web as a platform for research: Semantic approach - Ismail M.A.; Yaacob M.; Kareem S.A.; Nasaruddin F.H. (2023)
The access to internet has tremendously changed the way of information dissemination. The emergence of digital libraries and institutional repositories provides endless supplies of knowledge. Scholars in particular, make use of research output in the form of conference proceedings, journal and theses as references and guideline in generating new knowledge for the use of future generations. Novice researchers are the form of scholars which always drown in the ocean of information. This scholarly content resides on several heterogeneous databases that need to be integrated. Support in the early stage of study is crucial for novice researchers as it will give them some insights of where to seek for extra information based on institutions, people and research trend without having to go through tedious process of identifying this information all by themselves. Previous studies have identified support features that are useful for novice researchers among which are Relevant Literatures and Expert Detection. Thus, the purpose of this paper is to explore each of these support features and suggest state-of-the art development approach by utilizing Semantic Web technologies. The algorithms involved with each of the support features will be discussed. The result of the implementation shows significant information that can be utilized by novice researchers in accelerating research process. The evaluation of the information retrieved from the support features is elaborated. Future works in enhancing the proposed prototype are also discussed in the concluding remarks.